Energy and Mass Balance of Forni Glacier (Stelvio National Park, Italian Alps) from a Four-Year Meteorological Data Record - A. Senese; G. Diolaiuti; C. Mihalcea; C. Smiraglia (Arctic, Antarctic, and Alpine Research, 2012)
Since 26 September 2005 an Automatic Weather Station (AWS1 Forni) has been running on the ablation area of the largest Italian valley glacier, Forni, in the Ortles– Cevedale Group. A 4-year record (from 1 October 2005 to 30 September 2009) of air temperature, relative humidity, wind speed and direction, incoming and outgoing radiative fluxes, air pressure, liquid precipitation, and snow depth is considered. The meteorological data are analyzed to describe glacier surface conditions, to calculate the energy balance, and to evaluate the ice ablation amount. Snow accumulation was measured, thus permitting the estimation of the glacier point mass balance. An annual average amount of melt of 25.4 +- 0.021 m w.e. was calculated and an annual average amount of accumulation of +0.7 +- 0.006 m w.e. was measured at the AWS site. The annual average amount of mass balance was 24.7 +- 0.023 m w.e. Our analyses show that surface conditions during summer and fall seasons are important in regulating glacier albedo and then mass balance. In particular, snow cover presence, due to a longer persistence of spring snow, summer snowfalls and earlier fall solid precipitation, drives the duration of the ice melt period.